Persuasive Communication Strategies in Resolving Mosque Waqf Land Certification Problems: A Case Study at Religious Affairs Office Maiwa District, Enrekang Regency - Firman; Nurhikmah; Aris; Ramli; Muhammad Qadaruddin (LP2M IAIN Palopo, 2026)
This research is motivated by the many problems of uncertified mosque waqf land at the Maiwa District Office of Religious Affairs (KUA), Enrekang Regency. This study aims to examine the effectiveness of persuasive communication in minimizing the problems of mosque waqf land, including its forms, strategies, and supporting and inhibiting factors. This study uses a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, in-depth interviews, and documentation with informants consisting of the Head of the Maiwa District KUA, religious instructors, mosque administrators, religious leaders, and the local community. The results of the study indicate that persuasive communication implemented through interpersonal communication, group communication, organizational communication, and mass communication is considered effective in minimizing the problems of waqf land. Supporting factors for the effectiveness of persuasive communication include the role of the government, da'i, waqif, and nadzir, while inhibiting factors include the lack of competent human resources, low waqf literacy in the community, and the geographical conditions of the region. In addition, the persuasive communication strategies used, including the bil-hikmah (wisdom), al-mau'idzah hasanah (intelligible), al-mujadalah (intelligible), bil-hal (intelligible), bil-mal (intelligible), collaborative strategies, and the use of online media, have proven effective in resolving waqf land issues. This research highlights the importance of strengthening persuasive communication strategies and increasing waqf literacy to support the optimization of waqf land management in the community.